2021
DOI: 10.1038/s43247-021-00213-8
|View full text |Cite
|
Sign up to set email alerts
|

Extent of impact of deep-sea nodule mining midwater plumes is influenced by sediment loading, turbulence and thresholds

Abstract: Deep-sea polymetallic nodule mining research activity has substantially increased in recent years, but the expected level of environmental impact is still being established. One environmental concern is the discharge of a sediment plume into the midwater column. We performed a dedicated field study using sediment from the Clarion Clipperton Fracture Zone. The plume was monitored and tracked using both established and novel instrumentation, including acoustic and turbulence measurements. Our field studies revea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
46
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(64 citation statements)
references
References 60 publications
2
46
0
Order By: Relevance
“…The Multiresolution primitive equation regional ocean modeling system (MIT-MSEAS) model was used to predict the plume dispersion, i.e., direction, velocity, and concentration. Good agreement was found between the MIT-MSEAS model and the PLUMEX field experiments [23];…”
Section: Introductionmentioning
confidence: 70%
See 2 more Smart Citations
“…The Multiresolution primitive equation regional ocean modeling system (MIT-MSEAS) model was used to predict the plume dispersion, i.e., direction, velocity, and concentration. Good agreement was found between the MIT-MSEAS model and the PLUMEX field experiments [23];…”
Section: Introductionmentioning
confidence: 70%
“…The main differences between the two discharge sources in a polymetallic nodule mining operation are the orientation (vertical from the VTS and mostly horizontal from the PNMT), distance to the seabed, flow rate, and concentration of the suspended sediments. Some studies showed that the SWOE discharge location ranges from near the seabed to just below the oxygen minimum layer (800-1000 m water depth) [5,7,8,21], while the distance to the seabed of a PNMT depends on the discharge position on the PNMT, ranging from 1-3 m. The SWOE discharge flow rate and concentration are estimated to be about 0.56 m 3 /s and 8 g/L, respectively [21,23]. Table 1 shows the estimated solid flux rate and sediment concentration range of a PNMT discharge.…”
Section: Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, accidental waste spills of deep-sea sediment from the mining platform or riser pipe will most likely affect the pelagic environment. To date, the magnitude of the impact generated by mining activity is still unpredictable, as a full-scale mining test that includes a discharge into the midwater column has not yet been performed (Christiansen et al, 2020;Muñoz-Royo et al, 2021). Based on an estimation of 260 days per year of operation, a mining vessel could release up to 1.2 × 10 8 kg of sediment in the water column (Muñoz-Royo et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…To date, the magnitude of the impact generated by mining activity is still unpredictable, as a full-scale mining test that includes a discharge into the midwater column has not yet been performed (Christiansen et al, 2020;Muñoz-Royo et al, 2021). Based on an estimation of 260 days per year of operation, a mining vessel could release up to 1.2 × 10 8 kg of sediment in the water column (Muñoz-Royo et al, 2021). It has been suggested that a sediment plume released in the epipelagic layer will increase turbidity and decrease light penetration, resulting in a net decrease in primary productivity.…”
Section: Introductionmentioning
confidence: 99%